SIGNIFIKANSI PEMBENTUKAN KANDANG DENGAN SISTEM KOMUNAL BAGI MASYARAKAT DESA SUMBER SUKO KECAMATAN BELITANG KABUPATEN OKU TIMUR (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2020)
colony cage (communal) or group cage is a cage model in a cage room in which several cattle are placed, freely without being tied, functioning as a place of marriage and enlargement of children until weaned, or used as cages for enlargement and fattening. Group or communal model housing is expected to increase reproductive success and efficient use of labor. Sumber Suko Village is one of the villages located in the Belitang Sub-District of East OKU Regency where farmers communities there have begun to implement communal cage systems for their livestock. The high interest and desire of farmers to join in the maintenance of communal cage systems is an interesting phenomenon to be studied further. The researcher wanted to know what the benefits of the communal system were that encouraged cattle farmers to want to join the system of group cage maintenance. Based on the discussion above can be concluded as follows : (1) To find out the benefits of the housing system for Sumber Suko Village Community. (2) To find out how to maintain an approved internal communication systen in East OKU Regency. (3) To find out how to establish communication between group members who have one goal. How to improve efficiency in addition, members also get manure and also cow urine fermentation that serves to prevent the arrival of group plants as wel as getting assistance from the government in the from of free injection marriage, a feed chopper and bentor communication between group members by establishing effective, intensive communication. Effective communication is communication that can increase the productivity of farmers and communication, can resolve conflicts an can create a enducive environment.